Posttranslational and Therapeutic Control of Gasdermin-Mediated Pyroptosis and Inflammation - Fischer, Fabian A.; Chen, Kaiwen W.; Bezbradica, Jelena S. (Frontiers in Immunology, 2021)
Pyroptosis is a proinflammatory form of cell death, mediated by membrane pore-forming proteins called gasdermins. Gasdermin pores allow the release of the pro-inflammatory cytokines IL-1 and IL-18 and cause cell swelling and cell lysis leading to release of other intracellular proteins that act as alarmins to perpetuate inflammation. The best characterized, gasdermin D, forms pores via its N-terminal domain, generated after the cleavage of full length gasdermin D by caspase-1 or -11 (caspase-4/5 in humans) typically upon sensing of intracellular pathogens. Thus, gasdermins were originally thought to largely contribute to pathogen-induced inflammation. We now know that gasdermin family members can also be cleaved by other proteases, such as caspase-3, caspase-8 and granzymes, and that they contribute to sterile inflammation as well as inflammation in autoinflammatory diseases or during cancer immunotherapy. Here we briefly review how and when gasdermin pores are formed, and then focus on emerging endogenous mechanisms and therapeutic approaches that could be used to control pore formation, pyroptosis and downstream inflammation.